Educating consumers in self-testing: The development of an online decision aid. (July 2015) - Ickenroth, Martine HP; Grispen, Janaica EJ; Ronda, Gaby; Dinant, Geert-Jan; de Vries, Nanne K; van der Weijden, Trudy
Context and objective: Diagnostic self-tests have become available worldwide. The most frequently performed self-tests in the Netherlands are tests to detect high cholesterol and diabetes. Since these tests can be performed without professional guidance, potential consumers need to receive independent information on the pros and cons of self-testing. The aim of this study was to develop a decision aid (DA) on cholesterol and glucose self-testing to encourage informed choice and to meet consumers' needs and expectations. Methods: A DA was developed based on previous research and medical practice guidelines. The first prototype was assessed for content by means of semi-structured interviews with experts ( n = 13), followed by usability tests with users ( n = 10), leading to improvements to the DA in an iterative process. Results: Comments of the experts were grouped into four categories: general comments, textual remarks, technical errors and lay-out. User comments were mainly consistent with the experts' opinions. Important considerations that were identified concerned the safety of providing this information without direct professional counselling, whether a ranking of available tests should be provided and how strong a warning about self-testing should be. Conclusion: Important considerations on how to inform consumers about self-testing were discussed, and led to important changes in the DA. Future research will have to assess the actual use of the DA once it is accessible to the general public, as well as its effects on knowledge and attitude towards self-testing.